Effects of GABA Supplementation on Intestinal SIgA Secretion and Gut Microbiota in the Healthy and ETEC-Infected Weanling Piglets - Yuanyuan Zhao; Jing Wang; Hao Wang; Yonggang Huang; Ming Qi; Simeng Liao; Peng Bin; Yulong Yin (Mediators of Inflammation)
Pathogenic enterotoxigenic Escherichia coli (ETEC) has been considered a major cause of diarrhea which is a serious public health problem in humans and animals. This study was aimed at examining the effect of γ-aminobutyric acid (GABA) supplementation on intestinal secretory immunoglobulin A (SIgA) secretion and gut microbiota profile in healthy and ETEC-infected weaning piglets. A total of thirty-seven weaning piglets were randomly distributed into two groups fed with the basal diet or supplemented with 40 mg·kg−1 of GABA for three weeks, and some piglets were infected with ETEC at the last week. According to whether ETEC was inoculated or not, the experiment was divided into two stages (referred as CON1 and CON2 and GABA1 and GABA2). The growth performance, organ indices, amino acid levels, and biochemical parameters of serum, intestinal SIgA concentration, gut microbiota composition, and intestinal metabolites were analyzed at the end of each stage. We found that, in both the normal and ETEC-infected piglets, jejunal SIgA secretion and expression of some cytokines, such as IL-4, IL-13, and IL-17, were increased by GABA supplementation. Meanwhile, we observed that some low-abundance microbes, like Enterococcus and Bacteroidetes, were markedly increased in GABA-supplemented groups. KEGG enrichment analysis revealed that the nitrogen metabolism, sphingolipid signaling pathway, sphingolipid metabolism, and microbial metabolism in diverse environments were enriched in the GABA1 group. Further analysis revealed that alterations in microbial metabolism were closely correlated to changes in the abundances of Enterococcus and Bacteroidetes. In conclusion, GABA supplementation can enhance intestinal mucosal immunity by promoting jejunal SIgA secretion, which might be related with the T-cell-dependent pathway and altered gut microbiota structure and metabolism.